2018
DOI: 10.1155/2018/3523126
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Effect and Mechanism of Sophora moorcroftiana Alkaloids in Combination with Albendazole on Echinococcosis in an Experimental Rats Model

Abstract: Echinococcosis is a worldwide anthropozoonosis which is highly endemic over large animal husbandry areas in northwestern China. The current clinical therapeutic medicine against echinococcosis is albendazole, although it caused serious side effects in patients. The component in traditional Chinese herb medicine, Sophora moorcroftiana alkaloids (SA), is thought to be a potential drug to treat echinococcosis. In order to explore the effect and mechanism of SA treatment against echinococcosis, we established anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…As a result, the increased level of IL-2 after crocin treatment indicated that crocin had enhanced the host’s immunity against E. multilocularis . During the growth of AE metacestodes, multiple antigens are produced that directly infiltrate the host tissues around the metacestodes [ 38 ]. Consequently, the relative levels of IgE, IgM and IgG are enhanced following AE infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the increased level of IL-2 after crocin treatment indicated that crocin had enhanced the host’s immunity against E. multilocularis . During the growth of AE metacestodes, multiple antigens are produced that directly infiltrate the host tissues around the metacestodes [ 38 ]. Consequently, the relative levels of IgE, IgM and IgG are enhanced following AE infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These SNP markers or developed bin markers can be used for various processes, such as genetic map construction ( Ward et al, 2013 ), genome-wide association studies (GWAS) ( Sakiroglu & Brummer, 2017 ), and genome assembly. At present, GBS technology is an important tool for genotyping and is widely used in genetic linkage mapping, genetic selection ( Zhang et al, 2018a ; Zhang et al, 2018b ), genetic diversity studies ( Lu et al, 2013 ), germplasm identification ( Wu et al, 2014 ), species identification ( Pembleton et al, 2016 ) and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the species is currently the preferred drought-resistant afforestation tree species due to its strong adaptability to sand burial in the plateau ( Zhao, Zhang & Li, 2007 ), leading to its irreplaceable role in vegetation reestablishment programs aiming to stabilize shifting sand ( Liu et al, 1998 ). Meanwhile, the species has received much attention due to its medicinal properties ( Zhang et al, 2018a ; Zhang et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial properties of remedial herb medicines had been logically revealed in experiments with their oils, aqueous or alcoholic extracts, and other constituents (35). Clinically, albendazole was naturally used to treat echinococcosis with or without surgery, however, its severe side effects and poor solubility limit its application (36). The results revealed viability % of protoscolices treated with 20% hypertonic saline solution (actually used in our hospital) for 5 minutes was 43%, whereas, 16% of protoscolices were viable when treated with 60 µl/ml of seed's oil at the same time.…”
Section: Discussionmentioning
confidence: 99%